Exploring The Values and Practices Through Filipino Family Types among Grade 7 Students - Bersamina, El Niño L.; Hermosa, Jherwin P. (Future Science / FSH-PH Publications, 2024)
This research delves into the intricate dynamics of Filipino family types, DepEd core values, and Filipino family practices. In the Philip-pines, family structures have undergone significant transformations over the years. Traditional Filipino family structures, deeply rooted in cultural heritage and communal ties, have coexisted alongside the emergence of modern family structures influenced by urbanization, globalization, and shifting societal norms. Understanding the impact of these family structures on individuals, particularly students, is an area ripe for exploration.The found a positive correlation between nuclear families and ad-herence to DepEd values and practices. Extended families show a posi-tive correlation with pro-environmental attitudes, while single-parent families exhibit mixed results, including a negative correlation with cultural preservation. The study's significance lies in its contribution to understanding Filipino family dynamics and its potential to positively impact Filipino society by promoting cultural understanding and stronger family relationships.This study's significance lies in its contribution to understanding Filipino family dynamics, offering insights for future research, and promoting cultural understanding and stronger family relationships. It holds the potential to positively impact Filipino society by enriching educational experiences and fostering a deeper appreciation for diverse family structures and cultures.